Who should mark the homework? Concussion, conflicts of interest, and the constitution of expertise - Gregory Hollin (Critical Public Health)
Concussion in sport is increasingly understood as a public health crisis. A key facet of this crisis concerns the claim that industry-funded research results in conflicts of interest that fundamentally compromise scholarship. This poses a particular problem for policymakers when adjudicating upon who counts as an expert and what to do with the evidence that they provide. In this paper, I explore these matters in relation to the ‘Concussion in Sport’ report produced by the UK’s House of Commons’s Digital, Culture, Media and Sport Committee. I ask, first, which stakeholders submit evidence to the Committee and, second, how evidence provided by those stakeholders is marshalled within the report itself. I show that, despite concerns about conflicts of interest, a significant body of interdisciplinary scholarship is submitted to the Committee. The report itself, however, understands academic scholarship as being both deficient and compromised, drawing exclusively upon epidemiological and neuroscientific work. I conclude by suggesting such an approach compromises the committee’s own hope for an increasingly expansive notion of expertise.